Pomegranate peel extract alters the microbiome in mice and dysbiosis caused by Citrobacter rodentium infection. Issue 8 (7th July 2019) - George, Nadja S.; Cheung, Lumei; Luthria, Devanand L.; Santin, Monica; Dawson, Harry D.; Bhagwat, Arvind A.; Smith, Allen D.
Abstract: Treatment of mice with a pomegranate peel extract (PPX) decreased the pathogenicity of Citrobacter rodentium ( Cr ) infections. Here, we investigate the effects of PPX on the microbiome of uninfected or Cr ‐infected C3H/HeNCr mice by 16S rRNA gene sequencing. Mice were treated with water or PPX for 14 days, feces were collected, and then, the mice were infected with Cr and feces collected again at day 6 postinfection. DNA was isolated from the fecal samples and subjected to 16S rRNA gene sequencing to determine the microbial composition. Differences in the composition of the microbiome were observed for untreated and PPX‐treated mice with PPX mice having decreased diversity. PPX treatment decreased the Firmicutes/Bacteroidetes ratio by increasing Bacteroidetes and decreasing Firmicutes levels. The decrease in Firmicutes was driven by a large reduction in Lactobacillus . PPX treatment increased the abundance of Proteobacteria and Verrucomicrobiae and decreased Actinobacteria. The relative abundance of Cr reached 22% in water‐treated but only 5% in PPX‐treated infected mice. These results suggest that consumption of pomegranate polyphenols altered the microbiome, making it more resistant to displacement by infection with Cr, indicating that pomegranate polyphenols may mitigate the pathogenic effects of food‐borne bacterial pathogens. Abstract : Both treatment with pomegranate peel extract and infection with Citrobacter rodentium alter the microbiome of mice. Mice were treated with water or pomegranate peel extract for 14 days and fecal samples collected for microbiome analysis. Mice were then infected with Citrobacter rodentium, and fecal samples were collected at day 6 postinfection. The fecal microbiomes were analyzed by 16S rRNA gene sequencing. Weighted UniFrac plot of β‐diversity for water (blue), water‐infected (cyan), PPX (red), and PPX infected (magenta).